Rutaecarpine Ameliorates Ethanol-Induced Gastric Mucosal Injury in Mice by Modulating Genes Related to Inflammation, Oxidative Stress and Apoptosis - Ren, Sichen; Wei, Ying; Wang, Ruilin; Wei, Shizhang; Wen, Jianxia; Yang, Tao; Chen, Xing; Wu, Shihua; Jing, Manyi; Li, Haotian; Wang, Min; Zhao, Yanling (Frontiers in Pharmacology, 2020)
Background：Rutaecarpine (RUT), a major quinazolino carboline alkaloid compound from the dry unripe fruit Tetradium ruticarpum (A.Juss.) T.G.Hartley, has various pharmacological effects. The aim of this present study was to investigate the potential gastroprotective effect of rutaecarpine on ethanol-induced acute gastric mucosal injury in mice and associated molecular mechanisms, such as activating Nrf2 and Bcl-2 via PI3K/AKT signaling pathway and inhibiting NF-κB. Methods：Gastric ulcer index (UI) and histopathology was carried out to determine the efficacy of RUT in gastric ulceration, and the content of SOD, GSH in serum and MDA, MPO, TNF-α, IL-6, IL-1β in tissue were measured by kits. Besides, in order to illustrate the potential inflammatory, oxidative, and apoptotic perturbations, the mRNA levels of NF-κB p65, PI3K, AKT, Nrf2, Nqo1, HO-1, Bcl-2 and Bax were analyzed. In addition, the protein expression of NF-κB p65 and Nrf2 in cytoplasm and nucleus, AKT, p-AKT, Bcl-2 Bax and Caspase 3 were analyzed for further verification. Finally, immunofluorescence analysis was performed to further verify nuclear translocation of NF-κB p65. Results：Current data strongly demonstrated that RUT alleviated the gross gastric damage, ulcer index and the histopathology damage caused by ethanol. RUT inhibited the expression and nuclear translocation of NF-κB p65 and the expression of its downstream signals, such as TNF-α, IL-6, IL-1β and MPO. Immunofluorescence analysis also verifies the result. In the context of oxidative stress, RUT improved the antioxidant milieu by remarkably upregulating the expression Nqo1 and HO-1 with activating Nrf2, and could remarkably upregulate antioxidant SOD, GSH and downregulate levels of MDA. Additionally, RUT activate the expression of Bcl-2 and inhibited the expression of downstream signals Bax and Caspase 3 to promote gastric cellular survival. These were confirmed by RUT activation of the PI3K/AKT pathway manifested by enhanced expression of PI3K and promotion of AKT phosphorylation. Conclusion：Taken together, these results strongly demonstrated that RUT exerted a gastroprotective effect against gastric mucosal injury induced by ethanol. The underlying mechanism might be associated with the improvement of anti-inflammatory, anti-oxidation and anti-apoptosis system.